THE DYNAMICS OF HUMAN RELATIONSHIP: A NARRATIVE COMPARISON BETWEEN 'HILLS LIKE WHITE ELEPHANTS AND DEAD STARS' - Saputra, Taufan; Priyawan, Pepen; Pauji, Resa Restu (Saksama: Jurnal Sastra, 2024)
This research analyzes two short stories, "Hills Like White Elephants" by Ernest Hemingway and "Dead Stars" by Paz Marquez Benitez, with a focus on the influence of communication, perception, and cultural differences in shaping the dynamics of interpersonal relationships. Through a qualitative approach with content analysis, this research shows how ineffective communication and different perceptions can hinder the development of interpersonal relationships. Analysis shows that in both stories, unclear communication and promises to express feelings honestly lead to conflict and conflict. Apart from that, cultural differences and social values also play an important role in shaping the perceptions and actions of the characters in the story. The results of this research provide a deeper understanding of the complexity of human relationships in different cultural and temporal contexts.